Roentgenographic lung changes, asbestosis and mortality in a Belgian asbestos-cement factory. - Lacquet LM; van der Linden L; Lepoutre J (IARC scientific publications, 1980)
Annual chest radiographs, work history and mortality of 1,973 workers in an asbestos-cement factory were correlated with age and with duration and level of dust exposure. Degree of radiographic lung change was significantly related to fibre-years of exposure in the case of small lung opacities, pleural adhesions and pleural thickening. For 29 cases of asbestosis diagnosed between 1963 and 1977, a highly significant dose-response relationship was found. In comparison with national mortality rates, there was an excess of deaths due to cancer of the gastrointestinal tract, although there was no relationship to fibre-years.